2017
DOI: 10.1038/s41598-017-12581-3
|View full text |Cite|
|
Sign up to set email alerts
|

A new approach towards biomarker selection in estimation of human exposure to chiral chemicals: a case study of mephedrone

Abstract: Wastewater-based epidemiology is an innovative approach to estimate public health status using biomarker analysis in wastewater. A new compound detected in wastewater can be a potential biomarker of an emerging trend in public health. However, it is currently difficult to select new biomarkers mainly due to limited human metabolism data. This manuscript presents a new framework, which enables the identification and selection of new biomarkers of human exposure to drugs with scarce or unknown human metabolism d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…In the case of nor-mephedrone we found that the S-enantiomer is almost 2 times more abundant in the human urine sample compared to its R-counterpart; hence, normephedrone is predominantly excreted in its S-enantiomeric form. This novel finding is in excellent agreement with a recent report (Castrignano et al, 2017). Previously, we found that systemically administered nor-mephedrone exerts profound effects on extracellular serotonin, whereas the effects were less pronounced for dopamine (Mayer et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the case of nor-mephedrone we found that the S-enantiomer is almost 2 times more abundant in the human urine sample compared to its R-counterpart; hence, normephedrone is predominantly excreted in its S-enantiomeric form. This novel finding is in excellent agreement with a recent report (Castrignano et al, 2017). Previously, we found that systemically administered nor-mephedrone exerts profound effects on extracellular serotonin, whereas the effects were less pronounced for dopamine (Mayer et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…A recent study revealed that mephedrone undergoes stereospecific metabolism and the stereoisomers of nor-and 4-OH-mephedrone were detected in biological samples (Castrignano et al, 2017). Based on the differing potencies as inhibitors of SERTmediated uptake, we sought to perform release experiments with the stereoisomers of nor-and 4-OH-mephedrone in SERT-expressing HEK293 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, mephedrone was found to be enriched with the R-(+)-enantiomer in wastewater (EFww in 2014 (n=6)=0.57±0.02 and EFww in 2015 (n=4)=0.57±0.04). This indicates that mephedrone was consumed rather than directly disposed (Castrignanò, Mardal et al 2017) (see section S4 for further information).…”
Section: 3mephedronementioning
confidence: 99%